Sociodemographic variables, clinical features, and the role of preassessment cross-sex hormones in older trans people - Bouman, Walter Pierre; Claes, Laurence; Marshall, Ellen; Pinner, Gill T.; Longworth, Julia; Maddox, Victoria; Witcomb, Gemma; Jimenez-Murcia, Susana; Fernandez-Aranda, Fernando; Arcelus, Jon (Elsevier, 2016)
Introduction: As referrals to gender identity clinics have increased dramatically over the last few years, no studies focusing on older trans people seeking treatment are available. Aims: The aim of this study was to investigate the sociodemographic and clinical characteristics of older trans people attending a national service and to investigate the influence of cross-sex hormones (CHT) on psychopathology. Methods: Individuals over the age of 50 years old referred to a national gender identity clinic during a 30-month period were invited to complete a battery of questionnaires to measure psychopathology and clinical characteristics. Individuals on cross-sex hormones prior to the assessment were compared with those not on treatment for different variables measuring psychopathology. Main Outcome Measures: Sociodemographic and clinical variables and measures of depression and anxiety (Hospital Anxiety and Depression Scale), self-esteem (Rosenberg Self-Esteem Scale), victimization (Experiences of Transphobia Scale), social support (Multidimensional Scale of Perceived Social Support), interpersonal functioning (Inventory of Interpersonal Problems), and nonsuicidal self-injury (Self-Injury Questionnaire). Results: The sex ratio of trans females aged 50 years and older compared to trans males was 23.7:1. Trans males were removed for the analysis due to their small number (n ¼ 3). Participants included 71 trans females over the age of 50, of whom the vast majority were white, employed or retired, and divorced and had children. Trans females on CHT who came out as trans and transitioned at an earlier age were significantly less anxious, reported higher levels of self-esteem, and presented with fewer socialization problems. When controlling for socialization problems, differences in levels of anxiety but not self-esteem remained. Conclusion: The use of cross-sex hormones prior to seeking treatment is widespread among older trans females and appears to be associated with psychological benefits. Existing barriers to access CHT for older trans people may need to be re-examined.